PENGARUH NET PROFIT MARGIN (NPM) DAN DEBT TO EQUITY RATIO (DER) TERHADAP PERTUMBUHAN LABA PADA PT JAPFA COMFEED INDONESIA TBK PERIODE 2014 – 2023 - Fanny Keysha Septiyani; Arif Surahman (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of this study is ascertain how PT Japfa Comfeed Indonesia Tbk's profit growth impacted by DER and NPM, both partially and simultaneously, for the years 2014–2023. This study employed quantitative approach using secondary data from PT Japfa Comfeed Indonesia Tbk's 2014–2023 financial reports. Descriptive statistics, multiple linear regression, correlation coefficient, coefficient of determination, classical assumption testing, and hypothesis are among the data analysis methods employed in this study. According to the results of the coefficient of determination test, the DER and NPM account for 76.9% of profit growth, with other factors accounting for 23.1%. With sig. 0.004 < 0.05, the partial test (t-test) reveals t-value 4.287 > t-table 2.365, indicating that NPM has a positive partial effect on profit growth. On the other hand, the partial test (t-test) indicates that the DER has a negative impact on profit growth, with a sig. 0.138> 0.05, and a t-value 1.676 < t-table 2.365. With a sig. 0.006 < 0.05, the simultaneous test (F-test) reveals that the computed F-value of 11.638 is more than the F-table value of 4.46. Thus, the alternative hypothesis (Ha3) is supported and the null hypothesis (Ho3) is rejected, showing that the DER and NPM have a major impact on profit growth at PT Japfa Comfeed Indonesia Tbk from 2014 to 2023.